Prediction of fatal pancreatogenic shock in the first phase of the disease in patients with hyperergic inflammatory process in acute pancreatitis - A. N. Shcherbyuk; S. V. Morozov; A. V. Grishin; B. I. Yaremin; V. M. Manuylov; D. A. Tsarev; D. A. Mokhov; Ya. E. Nemstsveridze; A. A. Shcherbyuk (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2025)
Relevance. Acute pancreatitis occupies one of the leading places among acute surgical diseases, second in prevalence only to acute cholecystitis and appendicitis. This is one of the most difficult problems in emergency surgery. The overall mortality rate in acute pancreatitis varies from 5 to 10% depending on the proportion of its severe forms. Unfortunately, over the past 40 years, no significant results have been achieved in the treatment of this disease. Predicting fatal pancreatogenic shock in the first phase of the disease from the onset of acute pancreatitis is an important task for doctors, as it allows identifying patients at high risk of death and taking the necessary measures to stabilize the patient’s condition and improve the prognosis of his survival.Purpose of the study. To study clinical and biochemical parameters that can be predictors of fatal pancreatogenic shock. To determine the most effective methods of diagnostics and monitoring of patients with acute pancreatitis for timely detection of the risk of developing pancreatogenic shock. To study possible risk factors that can influence the development of fatal pancreatogenic shock in patients with acute pancreatitis in the first phase of the disease before the development of purulent complications. To develop a method for predicting fatal pancreatogenic shock using known prognostic scales based on the data obtained. The aim of the study was also to examine the effectiveness of predicting the hyperergic course of acute pancreatitis using common scales for assessing the severity of patients APACHE II, SAPS, MODS and SOFA, as well as to examine the effectiveness of the new scale developed by the authors of IDAP.Conclusions. A hyperergic reaction of the body to acute inflammation of the pancreas is likely if the degree of severity on the IDAP and APACH II scales is more than 9.0 and the ratio of severity in points to blood leukocytosis in SI units is >1.5. The applied scales for assessing the severity of acute pancreatitis adequately reflect changes in the severity of a patient with acute pancreatitis in the first phase of the disease and must be used without fail when planning treatment for patients.